Na, K-ATPase α3 is a death target of Alzheimer patient amyloid-β assembly - Ohnishi, Takayuki (2015)
Neurodegeneration correlates with Alzheimer’s disease (AD) symptoms, but the molecular identities of pathogenic amyloid β-protein (Aβ) oligomers and their targets, leading to neurodegeneration, remain unclear. Amylospheroids (ASPD) are AD patient-derived 10- to 15-nm spherical Aβ oligomers that cause selective degeneration of mature neurons. Here, we show that the ASPD target is neuron-specific Na+/K+-ATPase α3 subunit (NAKα3). ASPD-binding to NAKα3 impaired NAKα3-specific activity, activated N-type voltage-gated calcium channels, and caused mitochondrial calcium dyshomeostasis, tau abnormalities, and neurodegeneration. NMR and molecular modeling studies suggested that spherical ASPD contain N-terminal-Aβ–derived “thorns” responsible for target binding, which are distinct from low molecular-weight oligomers and dodecamers. The fourth extracellular loop (Ex4) region of NAKα3 encompassing Asn879 and Trp880 is essential for ASPD–NAKα3 interaction, because tetrapeptides mimicking this Ex4 region bound to the ASPD surface and blocked ASPD neurotoxicity. Our findings open up new possibilities for knowledge-based design of peptidomimetics that inhibit neurodegeneration in AD by blocking aberrant ASPD–NAKα3 interaction.